Comparison of Talc Pleurodesis versus Bleomycin in Malignant Pleural Effusion - Goni, Mohammad Osman; Islam, Mohammad Aminul; Alam, Kamrul; Hossain, Mohammad Zaid; Islam, Tazul; Islam, Kazi Saiful; Mahmud, Hossain Al; Kabir, Md Alamgir (Journal of Dhaka Medical College, 2020)
Back ground: Malignant pleural effusion can cause significant morbidity to terminal patients. Drainage and control pleural effusion can provide great palliation and improve the quality of life of these patients. The purpose of this study was to evaluate which agent, bleomycin or talc pouring for pleurodesis is superior in terms of effectiveness, safety and cost. Methods: It is a prospective randomized clinical trial from January 2013 to December 2014. A series of 38 patients entered in this trial. Inclusion criteria was diagnosed case of malignant pleural effusion either by fluid cytology or by pleural biopsy. Exclusion criteria was trapped lung, loculated effusions and life expectancy <1 month. Five grams of talc in 50ml of normal saline or 1 unit per kg body weight of bleomycin mixed in 50 ml of normal saline, was administered via chest tube thoracostomy after minimum drainage <100 ml daily in each patient. Treatment success was defined as the absence of recurrent pleural effusion on the chest radiography 1 month after pleurodesis. Results: Treatment success was achieved in 16 out of 18 patients (89%) in talc slurring group versus 14 out of 20 patients (70%) in the bleomycin group (p=0.154). Fever, pain and hypersensitivity were the side effects of pleurodesis. Conclusions: These results reflect that talc use was more effective than bleomycin in preventing early recurrence of malignant pleural effusions. Pleurodesis with talc instate of bleomycin can result in significant cost effective. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 42-48